The association between plasma homocysteine and coronary heart disease is modified by the MTHFR 677C>T polymorphism. Issue 23 (7th September 2013) - Mehlig, K; Leander, K; de Faire, U; Nyberg, F; Berg, C; Rosengren, A; Björck, L; Zetterberg, H; Blennow, K; Tognon, G; Torén, K; Strandhagen, E; et al.
Abstract : Objective: An elevated level of total plasma homocysteine (tHcy) has been associated with risk of coronary heart disease (CHD). The level of tHcy is affected by lifestyle, in addition to genetic predisposition. The methylene tetrahydrofolate reductase ( MTHFR ) 677C>T polymorphism (rs1801133) is among the strongest genetic predictors of tHcy. We examined whether the association between tHcy and CHD is modified by the MTHFR 677C>T polymorphism. Design and setting: Data from two case-control studies of first-time myocardial infarction (MI), Stockholm Heart Epidemiology Programme (SHEEP), and for MI and unstable angina, INTERGENE, were analysed in parallel. Patients: THcy was determined in a total of 1150 cases and 1753 controls. Interventions: None. Main outcome measures: The outcome comprised first-time MI and unstable angina, subsumed as CHD. Logistic regression was used to investigate the association between tHcy and CHD, and its modification by genotype. Results: High tHcy was confirmed to be a risk factor for CHD in both studies. In SHEEP, the association between tHcy and MI was observed in MTHFR 677 C-homozygotes (OR=1.4, 95% CI 1.2 to 1.6, for a difference by 1 SD of log tHcy) and in heterozygotes (OR=1.3, 95% CI 1.1 to 1.6) but not in T-homozygotes, independent of smoking, physical activity and obesity. An effect modification of similar magnitude was observed but not statistically significant in the smaller INTERGENE study, and confirmed in a meta-analysis of both studies. Conclusions: Two Swedish case-control studies showed that the association between elevated tHcy and CHD was confined to carriers of the MTHFR 677 C-allele, which could have implications for the efficiency of tHcy-lowering treatment.